Relevansi Hak Ijbar Wali Nikah ( Study Pemikiran Wahbah Az-Zuhaili Dalam Fiqih Islam Wa Adillatuhu) Dan Kompilasi Hukum Islam (KHI) - Ridwan Yunus, Moch. Aufal Hadliq KMW, (Mabahits : Jurnal Hukum Keluarga Islam, 2022)
In the anthropological perspective of Islamic law, which has a greater portion in the creation of law and the sustainability of the existence of law, it also has a contradictory perspective on the sustainability of the provisions of the guardian's ijbar rights. The values, norms and culture of today's society have given more position to women's determination. This means that the existence and role of women is now very much needed. Thus, the provisions of the right of ijbar that provide restraint to women are very contrary to the values, norms, and culture that exist in today's society. As a result, the right of ijbar cannot be accepted by various layers of society. The researcher chooses the type of research. In this library research, the researcher uses a qualitative library research approach. With data sources that include: primary data consists of Islamic Fiqh and the Compilation of Islamic Law (KHI). While secondary data in the form of, Islamic Marriage Law and others. Furthermore, the data that has been collected is analyzed by means of content analysis. Based on the research results are: (1). According to the thought of Wahbah az azuhaili, the right of ijbar or wali mujbir is assigned to a young girl even though she is a widow. the marriage of a woman who has reached puberty and is wise. He has the right to marry himself. While Jumhur is of the opinion that the one who marries her is her guardian. While the person who can force at this time is the father and the person he willed. does not have the right to force the marriage of virgins, minors, and insane persons other than the master, father, and other guardian whom he willed. (2). In the Compilation of Islamic Law (KHI) a guardian may not force his child's will to marry, in other words if a guardian wants to marry off his child there must be the willingness or permission of the bride and groom. This is mentioned in the Second Part of the Compilation of Islamic Law on Prospective Bride and Groom.